Factors Causing Forced Marriage of Minors : (Sociological Review of Law) - Gunarto; Hartiwiningsih (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Marriage is a bond that binds two human beings in a bond called household. Where the basic principle of a marriage is the agreement ofboth parties who will marry to unite the principles and responsibilities in running the household in the future. Children are gifts from Godthat are entrusted to both parents to be raised and educated according to the rules that apply. In the laws and regulations in Indonesia,children are also protected by the state regarding children's rights to live and get a decent life and education. In its journey there have beenso many cases of underage child marriages that have occurred due to forced marriages. The rise of forced marriage at an early age hasattracted the attention of all parties, both from the government and society, to address this problem. The high number of child marriages isa threat to the fulfillment of children's basic rights. The research method used is an normative research method with a legal sociologicalapproach. Early age forced marriages occur due to several factors, namely cultural factors, parents' wishes, lack of knowledge about positivelaw in Indonesia, incidents of immoral violations, and economic factors. Each of the factors that cause forced marriage at an early age hasan impact that can affect the child's survival.Keywords: Forced Marriage, Impact of Early Childhood Forced Marriage